Phage WO diversity and evolutionary forces associated with Wolbachia-infected crickets - Luo, Qing-Chen; Li, Yue-Yuan; Ren, Ye-Song; Yang, Xiao-Hui; Zhu, Dao-Hong (Frontiers in Microbiology, 2025)
IntroductionPhage WO represents the sole bacteriophage identified to infect Wolbachia, exerting a range of impacts on the ecological dynamics and evolutionary trajectories of its host. Given the extensive prevalence of Wolbachia across various species, phage WO is likely among the most prolific phage lineages within arthropod populations. To examine the diversity and evolutionary dynamics of phage WO, we conducted a screening for the presence of phage WO in Wolbachia-infected cricket species from China.MethodsThe presence of phage WO was detected using a PCR-based methodology. To elucidate the evolutionary forces driving phage WO diversity, analyses of intragenic recombination were conducted employing established recombination techniques, and horizontal transmission was investigated through comparative phylogenetic analysis of the phages and their hosts.Results and discussionOut of 19 cricket species infected with Wolbachia, 18 species were found to harbor phage WO. Notably, 13 of these 18 cricket species hosted multiple phage types, with the number of types ranging from two to 10, while the remaining five species harbored a single phage type. Twelve horizontal transmission events of phage WO were identified, wherein common phage WO types were shared among different Wolbachia strains. Notably, each phage WO horizontal transfer event was associated with distinct Wolbachia supergroups, specifically supergroups A, B, and F. Previous studies have found that four Wolbachia strains infect two to five species of crickets. However, among these cricket species, in addition to the shared phage WO types, all harbored species-specific phage WO types. This suggests that Wolbachia in crickets may acquire phage WO types through horizontal viral transfer between eukaryotes, independent of Wolbachia involvement. Furthermore, nine putative recombination events were identified across seven cricket species harboring multiple phage types. These findings suggest that horizontal transmission and intragenic recombination have played a significant role in the evolution of the phage WO genome, effectively enhancing the diversity of phage WO associated with crickets.